2022
DOI: 10.1128/mbio.00815-22
|View full text |Cite
|
Sign up to set email alerts
|

The Translational Landscape of SARS-CoV-2-infected Cells Reveals Suppression of Innate Immune Genes

Abstract: SARS-CoV-2 utilizes a number of strategies to modulate host responses to ensure efficient propagation. Here, we used ribosome profiling in SARS-CoV-2-infected cells to gain a deeper understanding of the translationally regulated events in infected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…Surprisingly, we and others observed a large increase in eIF2A protein abundance in SARS-CoV-2-infected cells 33,34 , while its mRNA level remained unchanged, suggesting either that eIF2A mRNA was more efficiently translated or that eIF2A protein became more stable upon infection. Interestingly, a recent study has shown a time-dependent increase in eIF2A mRNA translational efficiency after SARS-CoV-2 infection 35 ( Figure S4C ). The same study has also shown that –1 PRF efficiency, as measured by the relative ribosome footprint densities between ORF1A and ORF1B, is significantly increased at later time points during infection.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Surprisingly, we and others observed a large increase in eIF2A protein abundance in SARS-CoV-2-infected cells 33,34 , while its mRNA level remained unchanged, suggesting either that eIF2A mRNA was more efficiently translated or that eIF2A protein became more stable upon infection. Interestingly, a recent study has shown a time-dependent increase in eIF2A mRNA translational efficiency after SARS-CoV-2 infection 35 ( Figure S4C ). The same study has also shown that –1 PRF efficiency, as measured by the relative ribosome footprint densities between ORF1A and ORF1B, is significantly increased at later time points during infection.…”
Section: Discussionmentioning
confidence: 79%
“…Another proteomics study using Caco-2 cells has also shown that eIF2A protein abundance is progressively increased after SARS-CoV-2 infection 34 ( Figure S4B ). A third study by profiling ribosome occupancy has shown an increase in eIF2A mRNA translational efficiency after SARS-CoV-2 infection ( Figure S4C ) 35 . Consistent with these studies, we found that eIF2A protein abundance was increased in SARS-CoV-2-infected Vero E6 cells ( Figure 4A, B ), while its mRNA level remained unchanged ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It can be seen from Figure 14 that in more cells, the change of CAI is larger than zero (meaning that the CAI of the experimental group is higher than that of the control group), which indicates that maybe after virus infection, the gene expression of cells changes to be more conducive to virus translational elongation. Additionally, in the dataset of HBEC cells ( Puray-Chavez et al., 2022 ), the CAI values basically increase with the infection time and the CAI values in infected cells are all larger than control cells after 48 hours of infection. This is also strong evidence for the above conclusion.…”
Section: Resultsmentioning
confidence: 97%
“…However, the correlation between CAI and translational efficiency is maintained in cells infected with SARS-CoV-2. Thus, for studying the effect of viral infection on the translational elongation of SARS-CoV-2 mRNAs, we selected the gene expression datasets of the cells in the control state and the virus-infected state ( Daamen et al., 2021 ; Mulay et al., 2021 ; Sun et al., 2021 ; Puray-Chavez et al., 2022 ), and calculated the CAI values of the SARS-CoV-2 genomes in the corresponding cell datasets. The relative changes of CAI values in the control group and experimental group (virus infection) are consistent in different SARS-CoV-2 subtypes, and the relative positions of CAI values corresponding to ORFs are unchanged.…”
Section: Resultsmentioning
confidence: 99%